2022
DOI: 10.3390/nu14091955
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and Food Consumption Patterns and Their Associated Factors in the Tibetan Plateau Population: Results from 73 Counties with Agriculture and Animal Husbandry in Tibet, China

Abstract: Dietary imbalances are an important cause of morbidity and mortality, both in China and globally. Abnormal element content in the natural environment and the unbalanced dietary structure of populations coexist in the Tibetan Plateau. This study analyzed the dietary and food consumption patterns of 617 Tibetan residents and their associated factors. Cluster analysis revealed three modes of dietary pattern; the food consumption scores (FCSs) of subjects in modes with relatively high consumption frequency of stap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…The majority of the participants had acceptable food consumption scores (food security). This outcome is similar to that of Kong et al [ 19 ]. Findings from this study showed that adolescent males, peri-urban settlement, consumption of three or more meals per day and high food variety scores had higher odds for food security.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The majority of the participants had acceptable food consumption scores (food security). This outcome is similar to that of Kong et al [ 19 ]. Findings from this study showed that adolescent males, peri-urban settlement, consumption of three or more meals per day and high food variety scores had higher odds for food security.…”
Section: Discussionsupporting
confidence: 92%
“…It is based on dietary diversity, food frequency, and the relative nutritional relevance of the distinct food groups [17]. Residency, high-income level, income diversification, high education level, animal source of foods, good dietary practices and religion positively influenced food consumption scores [18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with previous reports (10), we observed a higher incidence of cholelithiasis speci cally in winter in Qinghai province. This phenomenon may be related to the high altitude, cold climate and highfat diet of this region (2,3,11). Cholelithiasis in Western countries is mainly caused by cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…The quality and safety of pork are closely related to people's lives. With the rise of large-scale swine farms worldwide, although the production of pork has been guaranteed, the taste and quality of pork have been continuously reduced [3,4]. Intramuscular fat (IMF) is an important indicator of pork quality, one of the important traits affecting pork quality, closely related to flavor, juiciness, tenderness, etc., determining the quality and nutritional value of pork [5]; however, it has not attracted sufficient attention on some pig farms.…”
Section: Introductionmentioning
confidence: 99%